(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2023)
Collimated thermal neutron beams are obtained from neutron extraction channels in nuclear reactors for various applications in research and technology, such as neutron imaging techniques (neutron radiography, neutron radioscopy, neutron tomography, and neutron-based autoradiography). Practical setups for neutron radiography using ion beams from particle accelerators and radioisotopic sources of fast neutrons have been also developed. However, only radioisotopic sources enable autonomous and transportable thermalization systems that can produce thermal neutron collimated beams. This work presents the performance results for a prototype of a compact system that generates a collimated beam of thermal neutrons using low-activity isotopic 241Am-Be sources. It was designed with the aid of Monte Carlo simulation using the PHITS v 3.17 program. Experimental measurements of the fluence of the neutron beam produced by the built prototype showed good agreement with the simulated values by the Monte Carlo method.